Carrion's disease : Inoculations Human Beings with Bartonella bacilliformis , A Review - Cuadra Calle, Manuel (2000)
On October 5, 1885 , at the time 112 years ago , succumbed Daniel Alcides Carrión , student of the 6th year of medicine as a result of the hitherto unknown anemic febrile form of the Peruvian wart that had been acquired by him through voluntary self-inoculation . Twenty-one days after the self-inoculation was practiced scarification two of each of his arms with bloody exudate obtained from a donor button verrucous a galloping febrile illness with anemia that led to his death was declared to the 19th day . The red blood cell count performed one day before his death showed just 1.085 million per mm3. Blood transfusion was advised that there was not conducted because the time was not yet technically handy resource. From his deathbed Carrión gave a message to the Peruvian doctors : " Not yet my friends have died , it is up to you to continue the work along the way I have commanded you ." The message has been captured and Carrión met along the 112 years following his death and shall continue for centuries to come .